GPS derived velocity field and strain rates of schirmacher glacier East Antarctica - Sunil, P.S.; Reddy, C.D.; Dhar, Ajay; Ponraj, M.; Selvaraj, C.; Jayapaul, D. (My University, 2010)
Monitoring of ice sheet velocity is one of the key issues to glacier dynamics understanding. Although the surface displacements of glaciers can be monitored Global Positioning System (GPS), this process is difficult in Antarctica due to logistic operations. Two GPS campaigns were conducted during the austral summer of 2003 and 2004 in the vicinity of Schirmacher Oasis, central Dronning Maud Land (cDML), East Antarctica to understand the velocity and strain rates of Schirmacher Glacier. GPS data was collected at 21 sites and have been analyzed to estimate the site co-ordinates, baselines and velocities. All the GPS sites on the glacier have been constrained, with the base station MAIT and the nearby IGS stations VESL and SYOG. Horizontal velocities of the glacier sites lie between 1.89±0.01 and 10.88±0.01 m/yr to the north north-east, with an average velocity of 6.21±0.01m/yr. The principal strain-rates provide a quantitative measurement of extension rates, which range from 0.11 ± 0.01 x 10'3 to 1.48 ± 0.85 x 10'3 y r 1 and shortening rates, which range from 0.04 ± 0.01 x 10 3 to 0.96 ± 0.16 x 1 O'3 y r 1. The velocity and strain rate distributions across the GPS network in the Schirmacher Glacier are spatially correlated with topography, subsurface undulations, fracture zones/crevasses and the partial blockage of the flow by nunataks and Schirmacher Oasis.
Keywords: GPS; Velocity; Schirmacher; Glacier; Antarctica; Maitri